Aberrant intra and inter network resting state functional connectivity in thyrotoxicosis. (28th January 2019) - Kumar, Mukesh; Rana, Poonam; Modi, Shilpi; Tyagi, Ritu; Kaur, Prabhjot; Kanwar, Ratnesh; Sekhri, Tarun; D'souza, Maria; Khushu, Subash
Abstract : Thyroid hormones epigenetically play an important role in the regularisation of neural networks and in neural differentiation during brain development. The present study aimed to explore the intra and inter network resting state functional connectivity changes underlying the neurobehavioural symptoms in thyrotoxicosis. To understand the pathophysiological changes, we investigated the correlation between functional connectivity and clinical and behavioural measures. Twenty‐eight freshly diagnosed thyrotoxicosis patients suffering with symptoms such as palpitation, loss of weight, trembling and heat intolerance from days to weeks and 28 healthy controls were recruited for the study. Thyrotoxicosis patients showed significantly decreased functional connectivity in sensorimotor network, fronto‐temporal network, default mode network, right fronto‐parietal network, left fronto‐parietal network and salience network. Inter network functional connectivity was significantly reduced between the basal ganglia network and sensorimotor network and increased between the salience network and fronto‐temporal network in thyrotoxicosis. Cognitive functions such as visual retention, recognition of objects, mental balance and performance on neuropsychological tests (ie, the Bender Gestalt test, Nahar‐Benson test and Mini Mental State Examination) also showed significant decline in thyrotoxicosis patients. The altered intrinsic resting state functional connectivity might underlie these cognitive deficits. The increased functional connectivity between the salience network and fronto‐temporal network suggests the recruitment of additional neuronal circuitry needed to compensate for the neuropathology in the primary neural network in thyrotoxicosis.